If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 3x + -20 Multiply f * x fx = 3x + -20 Reorder the terms: fx = -20 + 3x Solving fx = -20 + 3x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -20x-1 + 3 Simplifying f = -20x-1 + 3 Reorder the terms: f = 3 + -20x-1
| 5c^3+20c^2-105c=0 | | -3x-y=9 | | 8y+17=3y-3 | | 4x-3(x-1)=9x+15-7x | | 2r^2+r-15=0 | | (0.4x)-(2x)-(.8)=1.4 | | 9(d+8)= | | 2(3x+2)=6x+5 | | f(x)=4x-8 | | 5(d-5)+6= | | n=0.08*7496+7400 | | 6x+9y=15 | | 2(3x+2)=6x+2 | | 2.00+x*.30=12.50 | | 14=2+x | | 2(x-5)+7=8x | | 2b-6-11b-5= | | -3(t-2)+6t=7t-4 | | (5-6m)/m^2-9 | | 9(x+5)=8(x-6)+x | | f(16)=4x-8 | | 4(X+7)=2 | | 14a+16a= | | 9(x-5)=8(x-6)-x | | n^2-2-12=0 | | 5(2+x)+3x=-2(x+5) | | -3(-x+2)=2x-4 | | 176r=16 | | 5y+4x=1 | | -4t(t-2)+6t=8t-3 | | 7x+4y+8= | | Y-9.98=2.85 |